Multi-omics analysis revealed potential use of immunotherapy and CDK4/6 inhibitors in intimal sarcoma - Wang, Bei; Chen, Rongrong; Yin, Huan; Chang, Ziyi; Liu, Yao; Zhong, Dingrong; Li, Feng (Frontiers in Immunology, 2025)
BackgroundIntimal sarcoma (IS) and angiosarcoma (AS), two rare yet highly aggressive vascular mesenchymal malignancies, present significant therapeutic challenges due to their scarcity, which underscoring the urgent need to investigate genetic alterations and tumor microenvironment (TME) features for novel therapeutic development.MethodsWe performed integrated analysis of whole-exome sequencing (WES)/1021-gene panel sequencing, RNA sequencing, and immunohistochemistry (IHC) data from 31 IS and 35 AS patients to identify potential precision therapy.ResultsGenomic profiling revealed 522 and 518 single nucleotide variants (SNVs) in the IS and AS cohorts, respectively. TP53 mutations predominated in AS versus IS (15/35 vs 2/31, p < 0.001). Conversely, IS exhibited significantly more copy number variants (CNVs), particularly involving the KDR/KIT/PDGFRA locus (chromosome 4) and the CDK4/MDM2 locus (chromosome 12) (p < 0.001). Strikingly, 25/31 (81%) IS patients harbored CDK4 copy number gains or CDKN2A/B losses, compared to only 2/35 (6%) AS patients (p < 0.001). TME analysis revealed no significant inter-group differences overall; however, pulmonary artery IS specimens demonstrated substantial immune infiltration. Notably, reduced CD3+ T-cell density correlated with shorter survival (p =0.029). PD-L1 expression analysis (≥1% cutoff) showed positivity in 6/8 evaluable patients, including 3 with >50% tumor cell staining. Two IS patients receiving postoperative Sintilimab (PD-1 inhibitor) experienced prolonged survival (overall survival: 14+ and 56+ months, respectively).ConclusionsThis study characterizes the distinct mutation landscape yet similar immune microenvironment of rare IS and AS. Given the frequent cell cycle dysregulation and the observed PD-L1 expression in a subset of patients, CDK4/6 inhibitors and PD-1/PD-L1 inhibitors warrant further clinical investigation for these patients.